Conceptual model of a manufacturing enterprise’s digital ecosystem in the context of Industry 4.0. - Loza, S. (Економічний вісник Донбасу, 2025)
This article proposes an integrated model of manufacturing enterprise transformation that synthesises ecosystem interaction logic with technical and organisational aspects of Fourth Industrial Revolution technology implementation. The topic's relevance is determined by the transition from traditional value chains to network forms of collaboration, where enterprises function as participants in complex digital ecosystems. The research addresses how manufacturing organisations can systematically integrate into digital networks whilst simultaneously transforming internal processes and technological infrastructure. The methodological foundation comprises the combination of OCO Theory for ecosystem integration mechanisms through orientation, cooperation, and orchestration of digital resources, DSE Framework for structuring organisational changes across five transformation trajectories with tri-aspect outputs, and Knowledge-Based View for competence reconfiguration processes through external engagement and internal knowledge creation. The proposed model structures interaction across four levels – from the external ecosystem environment with micro- and macro-influence factors through integration mechanisms and organisational trajectories to specific technological architecture of production systems, built on principles of interoperability, virtualisation, decentralisation, real-time operation, service orientation, and modularity. The work's novelty lies in conceptualising end-to-end knowledge management processes that permeate all model levels and ensure bidirectional connection between external ecosystem resources and internal organisational capabilities through mechanisms of exploiting existing competencies and exploring new opportunities. The model is intended for use in strategic planning and can serve as a foundation for making decisions regarding prioritising investments in digital technologies considering ecosystem context and national economy specifics. У цій статті пропонується інтегрована модель трансформації виробничих підприємств, яка синтезує логіку взаємодії екосистеми з технічними та організаційними аспектами впровадження технологій Четвертої промислової революції. Актуальність теми визначається переходом від традиційних ланцюгів створення вартості до мережевих форм співпраці, де підприємства функціонують як учасники складних цифрових екосистем. Дослідження стосується того, як виробничі організації можуть систематично інтегруватися в цифрові мережі, одночасно трансформуючи внутрішні процеси та технологічну інфраструктуру. Методологічна основа включає поєднання теорії OCO для механізмів інтеграції екосистеми через орієнтацію, співпрацю та оркестрацію цифрових ресурсів, рамки DSE для структурування організаційних змін за п'ятьма траєкторіями трансформації з триаспектними результатами та погляду на основі знань для процесів реконфігурації компетенцій через зовнішню взаємодію та внутрішнє створення знань. Запропонована модель структурує взаємодію на чотирьох рівнях – від зовнішнього середовища екосистеми з мікро- та макрофакторами впливу через механізми інтеграції та організаційні траєкторії до конкретної технологічної архітектури виробничих систем, побудованої на принципах сумісності, віртуалізації, децентралізації, роботи в режимі реального часу, орієнтації на сервіс та модульності. Новизна роботи полягає в концептуалізації процесів управління знаннями від початку до кінця, які пронизують усі рівні моделі та забезпечують двонаправлений зв'язок між зовнішніми ресурсами екосистеми та внутрішніми можливостями організації через механізми використання існуючих компетенцій та дослідження нових можливостей. Модель призначена для використання у стратегічному плануванні та може слугувати основою для прийняття рішень щодо пріоритетності інвестицій у цифрові технології з урахуванням контексту екосистеми та специфіки національної економіки.